2014
DOI: 10.1371/journal.pgen.1004102
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Functional Annotation of 77 Prostate Cancer Risk Loci

Abstract: Genome-wide association studies (GWAS) have revolutionized the field of cancer genetics, but the causal links between increased genetic risk and onset/progression of disease processes remain to be identified. Here we report the first step in such an endeavor for prostate cancer. We provide a comprehensive annotation of the 77 known risk loci, based upon highly correlated variants in biologically relevant chromatin annotations— we identified 727 such potentially functional SNPs. We also provide a detailed accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
158
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(166 citation statements)
references
References 86 publications
5
158
1
1
Order By: Relevance
“…Furthermore, this multi-cancer risk locus has also been identified in a smaller scale study of oesophageal squamous cell carcinoma in Chinese populations (Table 1; Zhou et al 2013). Results of an in silico annotation of multiple prostate cancer risk loci indicated MDM4 rs4245739 to be the causal (functional) SNP at this GWAS identified region, though no experimental evidence has yet been provided to demonstrate the prostatic function of this polymorphism (Hazelett et al 2013). In ovarian cancer, Wynendaele et al (2010) previously demonstrated a mechanism of microRNA (miRNA) regulation by which miR-191-5p showed a greater affinity for the MDM4 rs4245739 SNP C-allele, resulting in higher levels of MDM4 expression from the risk-associated A-allele.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, this multi-cancer risk locus has also been identified in a smaller scale study of oesophageal squamous cell carcinoma in Chinese populations (Table 1; Zhou et al 2013). Results of an in silico annotation of multiple prostate cancer risk loci indicated MDM4 rs4245739 to be the causal (functional) SNP at this GWAS identified region, though no experimental evidence has yet been provided to demonstrate the prostatic function of this polymorphism (Hazelett et al 2013). In ovarian cancer, Wynendaele et al (2010) previously demonstrated a mechanism of microRNA (miRNA) regulation by which miR-191-5p showed a greater affinity for the MDM4 rs4245739 SNP C-allele, resulting in higher levels of MDM4 expression from the risk-associated A-allele.…”
Section: Introductionmentioning
confidence: 91%
“…The numbers shown in the parentheses correspond to the average number of SNPs required to identify 50 and 80% of the causal SNPs, respectively. histone methylation (He et al 2010;Wang et al 2011;Bert et al 2013;Hazelett et al 2014), and transcription factor bindings (Tan et al 2012; The ENCODE Project Consortium 2012; Sharma et al 2013;Hazelett et al 2014;Takayama et al 2014). All annotations were aligned to human genome version 19 coordinates.…”
Section: Annotations Used For Eqtl Datamentioning
confidence: 99%
“…The prevalence of PCa differs significantly among populations, indicating that the host's genetic background may play an important role in susceptibility to PCa (2). Single-nucleotide polymorphisms (SNPs) are the most common type of genetic variations in human genome, and they have been found to be associated with the risk of PCa (3)(4)(5)(6). Genome tiling arrays have indicated that 1% of the human genome is composed of protein-coding sequences and ~4-9% of the sequences of the human genome are transcribed to non-coding RNAs (ncRNAs) (7).…”
Section: Introductionmentioning
confidence: 99%